Power shift : China and Asia's new dynamics - Shambaugh, David L. (University of California Press, 2006)
The dynamics of international relations in Asia are undergoing broad and fundamental changes that are reverberating around the world. Primary among the catalysts of change in the region is the rise of China as the engine of regional economic growth, as a major military power, as a significant voice in regional diplomacy, and as a proactive power in multilateral institutions. With in-depth assessments by seventeen of the world's leading experts on China's foreign relations, this groundbreaking volume offers the most timely, up-to-date, and comprehensive analysis of China's emerging influence on.